Formulation and Evaluation of a Topical Herbal Gel Containing Rosmarinus Officinalis for Anti-inflammatory Activity - Wedad Saleh; Darine Abozaid; Ahmed Aljaiyash; Azzah Ali (AlQalam Journal of Medical and Applied Sciences, 2026)
From antiquated uses to contemporary pharmaceutical technologies, topical medication administration has undergone substantial change. It has long been known that products can have systemic or local effects when applied topically. The development of devices that can carry solutes across this barrier in a targeted manner and with measured accuracy at specific sites within the skin and beyond has been made easier by our growing understanding of the architecture and physiology of the skin. In contrast to diclofenac sodium, which showed an inhibition of 86.09% at 800 µg/mL, Rosmarinus officinalis ethanolic extract showed a concentration-dependent inhibition of protein denaturation, reaching a maximum inhibition of 71.08% at a dosage of 500 µg/mL. The topical gel formulations were prepared using a variety of gelling agents at different concentrations. Out of the six formulations that were made, F4 and F6 showed outstanding physicochemical characteristics, including ideal pH, good spreadability, appropriate viscosity, and no signs of skin irritation. The findings imply that F4 and F6 are the ideal polymeric bases for topical distribution and that rosemary extract may have a notable anti-inflammatory impact.